2020
DOI: 10.2174/1874467212666191113150553
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Spironolactone on Markers of Myocardial Oxidative Status, Inflammation and Remodeling in Hyperthyroid Rats

Abstract: Background: Hyperthyroidism promotes the development and progression of cardiovascular diseases (CVD). Aldosterone, a key mediator of myocardial inflammation, oxidative stress and fibrosis, may be activated in hyperthyroidism. Objective: To assess the impact of hyperthyroidism on aldosterone levels and myocardial oxidative status, inflammatory and fibrotic markers in hyperthyroid rats, and to test if th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…In a hyperthyroid Wistar rat model induced by intraperitoneal injection with exogenous thyroxine for 4 weeks, cardiac lipid peroxides and serum endothelin-1 were increased, whereas cardiac superoxide dismutase, catalase, glutathione, and matrix metalloproteinase-2 were reduced in the hyperthyroid group. Unfortunately, myocardial inflammation (MPO level) and fibrosis (Masson trichrome staining) did not change significantly compared with the controls ( 57 ). Interestingly, hypothyroidism rats seem to be related with significant sterile inflammatory changes (leukocyte infiltration) in cardiac tissue ( 58 ).…”
Section: Discussionmentioning
confidence: 89%
“…In a hyperthyroid Wistar rat model induced by intraperitoneal injection with exogenous thyroxine for 4 weeks, cardiac lipid peroxides and serum endothelin-1 were increased, whereas cardiac superoxide dismutase, catalase, glutathione, and matrix metalloproteinase-2 were reduced in the hyperthyroid group. Unfortunately, myocardial inflammation (MPO level) and fibrosis (Masson trichrome staining) did not change significantly compared with the controls ( 57 ). Interestingly, hypothyroidism rats seem to be related with significant sterile inflammatory changes (leukocyte infiltration) in cardiac tissue ( 58 ).…”
Section: Discussionmentioning
confidence: 89%
“…It has been shown that spironolactone exhibits antioxidant activity and protects organs against oxidative stress by inhibiting the production of free radicals [69]. There is also a substantial amount of evidence from animal models that spironolactone can play a role in the reduction in oxidative stress and antioxidant defenses, e.g., in hyperthyroid rats [75]. Moreover, spironolactone has long been shown to inhibit aldosterone-induced oxidative stress in human endothelial cells [76].…”
Section: Oxidative Stressmentioning
confidence: 99%
“…However, its use particularly at higher dose has been associated with intermenstrual bleeding due to reduction in production of estradiol and endometrial thickness [23,24]. Interestingly, a number of studies, including recent studies from our laboratory animals have demonstrated the effectiveness and safety of low-dose SPL against endocrine disruption in PCOS models [25][26][27][28]. However, the effects of low-dose SPL on PCOS-associated adipose dysfunction is unknown.…”
Section: Introductionmentioning
confidence: 99%